"Which Men?" How an Intersectional Perspective on Men and Masculinities Helps Explain Women's Political Underrepresentation. Issue 2 (22nd June 2018) - Childs, Sarah; Hughes, Melanie
Abstract : Progress toward gender equality in politics is striking. With the help of electoral gender quotas in more than 130 countries, women's national legislative representation more than doubled in the last 20 years. Other historically marginalized groups—racial, ethnic, and religious minorities, immigrants, and indigenous peoples—are also increasingly making their way into our parliaments. Political institutions are, then, more inclusive today than they have ever been. Yet equal representation has not been fully realized: some marginalized groups have seen a decline, and men from dominant social and economic groups—hereafter "elite men"—remain numerically dominant. Globally, there are no known cases in which elite men do not hold a disproportionately high share of positions in national elective office (Hughes 2015).